Emergency Treatment of Burns in Adults—Characteristics of Adult Patients and Acute/Pre-Hospital Burn Management - Bogdan Oprita; Georgeta Burlacu; Vlad Mircea Ispas; Ioana Adriana Serban; Ruxandra Oprita (European Burn Journal)
Background: Burns represent one of the most severe injuries encountered in the pre-hospital and ED environment, with essential features and an often negatively powerful impact on patients’ quality of life. Preventive measures can significantly reduce the number of cases presenting to medical facilities; knowledge and the correct application of first aid measures in the pre-hospital stage have a significant role in reducing the risk of complications and in obtaining optimal outcomes. Methods: This retrospective one-year single-center study analyzed 399 adult burn patients treated at the Clinical Emergency Hospital of Bucharest (CEHB) in 2023. Information concerning the main characteristics of the patients (age, sex, and residence), etiology and severity of burns, and pre-hospital management of patients was analyzed. Results: Most patients (63.41%) resided in urban areas, with a higher prevalence of males (55.89%). Thermal burns accounted for 77.69% of cases, primarily caused by water, food, oil, or flames. Burns covered ≤10% TBSA in 77.19% of cases, while 6.52% extended beyond 50% TBSA. First aid was provided to 52.63% of patients at the accident site, often by non-specialized individuals. The mean time to presentation was 34.90 h, with significant correlations between time, age, burned body surface area, and burn depth. Conclusions: There is a real need for improvements in first-aid training and health initiatives to enhance pre-hospital burn care. Better documentation of the care provided to patients before being admitted to specialized centers, as well as further studies in this field, are absolutely necessary for improving prevention programs and burn management in the acute stage.